Comparative Solid Phase Photocatalytic Degradation of Polythene Films with Doped and Undoped TiO2 Nanoparticles. (25th May 2010) - Asghar, Wasim; Qazi, Ishtiaq A.; Ilyas, Hassan; Khan, Aftab Ahmad; Awan, M. Ali; Rizwan Aslam, M.
Abstract : Comparative photocatalytic degradation of polythene films was investigated with undoped and metal (Fe, Ag, and Fe/Ag mix) doped TiO2 nanoparticles under three different conditions such as UV radiation, artificial light, and darkness. Prepared photocatalysts were characterized by XRD, SEM, and EDS techniques. Photocatalytic degradation of the polythene films was determined by monitoring their weight reduction, SEM analysis, and FTIR spectroscopy. Weight of PE films steadily decreased and led to maximum of 14.34% reduction under UV irradiation with Fe/Ag mix doped TiO2 nanoparticles and maximum of 14.28% reduction under artificial light with Ag doped TiO2 nanoparticles in 300 hrs. No weight reduction was observed under darkness. Results reveal that polythene-TiO2 compositing with metal doping has the potential to degrade the polythene waste under irradiation without any pollution.